2008
DOI: 10.1148/rg.285075217
|View full text |Cite
|
Sign up to set email alerts
|

Athletic Pubalgia and “Sports Hernia”: Optimal MR Imaging Technique and Findings

Abstract: Groin injuries are common in athletes who participate in sports that require twisting at the waist, sudden and sharp changes in direction, and side-to-side ambulation. Such injuries frequently lead to debilitating pain and lost playing time, and they may be difficult to diagnose. Diagnostic confusion often arises from the complex anatomy and biomechanics of the pubic symphysis region, the large number of potential sources of groin pain, and the similarity of symptoms in athletes with different types or sites o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
219
0
12

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 234 publications
(233 citation statements)
references
References 66 publications
2
219
0
12
Order By: Relevance
“…Dulucq et al [29] showed acceptable complication and recurrence rates after TEP repair in 3,100 patients. During TAPP repair, there is an advantage of diagnosing and repairing unexpected contralateral hernias in patients with unilateral hernias, which has been reported to occur in 25-50% of patients [47,48].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Dulucq et al [29] showed acceptable complication and recurrence rates after TEP repair in 3,100 patients. During TAPP repair, there is an advantage of diagnosing and repairing unexpected contralateral hernias in patients with unilateral hernias, which has been reported to occur in 25-50% of patients [47,48].…”
Section: Discussionmentioning
confidence: 99%
“…Quite often, substantial funicular lipomas or pre-/or retroperitoneal fat prolapse into the enlarged hernia orifices ring [45][46][47][48]. They should be retracted and eventually resected, because they may become symptomatic or mimic a recurrent hernia [49].…”
Section: Indirect Hernias Statements Recommendationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Groin pain is a very early complaint of patients suffering from FAI but its differential diagnosis is very wide: stress fractures of the femoral neck, iliopsoas tendonitis, tears of the adductor tendons, nerve entrapment syndromes and inguinal hernia are only a few of the possible underlying conditions leading to groin pain, especially in athletes [18]. Therefore, a history of groin pain is an early, but non-specific finding of FAI.…”
Section: Introductionmentioning
confidence: 99%
“…It consists of appropriately oriented weight bearing anteroposterior (AP) pelvis, a Dunn lateral, and a false profile view [3] . It may depict subchondral sclerosis, symphyseal lytic changes and widening or narrowing of the joint space, especially in the chronic phase of the disease [18,32,33] . Another proposed radiographic view, with major contribution to the pubic instability evaluation is the flamingo view in double and single leg stance positions [11,34] .…”
Section: Radiographic Analysismentioning
confidence: 99%